Urban Flood Susceptibility Analysis Using Multi Criteria Decision Analytical Hierarchy Process (AHP) Method: Case Study of Bandung City - Agustina, Rena Denya; Putra, Riki Purnama; Susanti, Seni; Setyadji, Agustinus Bambang; Virtriana, Riantini (Geoplanning: Journal of Geomatics and Planning, 2025)
Flood is one of the natural disasters and is supported by bad human habits, of course, this disaster can cause enormous losses, which can take lives. Flood handling certainly requires proper analysis before handling is carried out. Various methods for mapping flood susceptibility can be done, one of which is using the AHP Multi-Criteria Decision method which is considered the most up-to-date and very accurate method in terms of accuracy. This study aims to map the susceptibility of flood hazard in urban areas, especially in the city of Bandung with the help of satellite imagery. The method in this study uses the AHP Multi-Criteria Decision method, where five experts are needed to carry out an assessment in determining the variable weight value, with the variable in question namely; (1) TWI; (2) Elevations; (3) Slopes; (4) Precipitation; (5) Land Cover; (6) NDVI; (7) Distance from Rivers; and (8) Distance from Roads. In addition, this study validates the results of the mapping by comparing the real events of flooding in the city of Bandung in 2002-2022 with the map of the susceptibility of flood hazard in the city of Bandung. The results obtained in this study are flood hazard susceptibility maps created well with validation of 80.20%. In addition, areas that are very at hazard of being affected by flooding are the East Bandung area (Mandalajati, Ujungberung, Cibiru, Gedebage, and Panyileukan) with a high hazard of over 75%, and an extreme hazard of above 0.1%.